Tyrone claims that the first step to simplify this expression
1 answer:
Answer:
1/(m^4*n^2
Step-by-step explanation:
The given expression is
(m^2*n^-3)/(m^6*n^-1)
Tyrone's approach.
Raising the expression to the 3rd power will not help. It will make the expression more complicated.
Alisha's approach.
(m^2*n^-2)/(m^6*n^-1)
= m^(2-6)*n^(-3+1)
= m^-4*n^-2
= 1/(m^4*n^2)
Alisha's approach will simplify the expression to 1/(m^4*n^2
You might be interested in
Which could be the vertices of triangle W? A. X(–2, 2), Y(–10, 2), Z(–6, 10) B. X(2, 2), Y(4, 2), Z(3, 4) C. X(0, 2), Y(4, 2), Z
kirill [66]
Answer:
A. B. C. D. E. F. G. H. I. J. K. L. M. N. O. P. Q. R. S. T. U. V. W. X. Y. Z
Answer:
Step-by-step explanation:
You would have to divide 34.5 and 5 to be able to find out what each pencil measurement the answer is 6.9.
8*2=16
8*8=64
d+d+d=3d
16+64=80d3rd
In thirty months you should have 5,250.00